The Munsters. Season one [videorecording (DVD)] - Liebmann, Norm; Haas, Ed; Burns, Allan, 1935-2021; Hayward, Chris (Universal Studios Home Entertainment, 2013)
The Munsters are America's first family of fright! There's Herman, devoted dad and 'working stiff'; Lily, the sassy homemaker; Grandpa, a former count who still loves to take a bite out of life; Marilyn, the 'black sheep' of the family; and Eddie, the little boy who loves to have a howling good time.